The hydroelastic analysis of marine propellers with consideration of the effect of the shaft. (1st February 2017) - Zou, Donglin; Zhang, Jianbo; Ta, Na; Rao, Zhushi
Abstract: At present, most studies on the hydroelastic analysis of marine propellers do not consider the effect of the shaft. So in this paper, with consideration of the effect of the shaft and bearings, a fluid–structure interaction model of the marine propeller is established by coupled boundary element method (BEM) and finite element method (FEM). The hydroelastic performance of the propeller is discussed with and without consideration of the shaft and bearings. The research shows that the natural frequencies of the blade attached at the shaft are slightly less than those without shaft. This would be more prominent as the shaft's flexibility is increased. There are some errors for the hydroelastic performance of propellers if the shaft and bearings are ignored. So the shaft should not be neglected in the prediction of the propellers' hydroelastic performance. Highlights: The shaft and bearings are considered for the first time in the fluid–structure interaction model of the marine propeller. The natural frequencies of the blade attached at the shaft are slightly less than those with root fixed. There are some errors for the hydroelastic performance of propellers if the shaft and bearings are ignored.